A new species of the shrimp genus Typton Costa, 1844 (Malacostraca, Decapoda, Palaemonidae) from the Cabo Verde Archipelago - Neves, Keider (Zootaxa, 2020)
A new species of sponge-dwelling palaemonid shrimp of the genus Typton Costa, 1844 is described based on specimens collected in Enseada de Corais da Matiota, São Vicente Island, Cabo Verde. Typton anaramosae sp. nov., is the twentieth species known in this genus and is morphologically most similar to T. prionurus from the western Atlantic and T. granulosus and T. serratus from the eastern Pacific, all four sharing the serrated distal part of the outer margin of the uropodal exopod and the absence of a median tooth on the posterodorsal margin of the sixth pleonite. The more specific features, which distinguish the new species from its related congeners are discussed.